Distributed Data Aggregation protocol for improving lifetime of Wireless Sensor Networks - Ali K. M. Al-Qurabat; Ali Kadhum Idrees (QALAAI ZANIST JOURNAL, 2021)
In Wireless Sensor Networks (WSN), the deployed sensor nodes can sense the same measures from the monitored area and forward these redundant measures to the sink node. Although redundant measures provide better accuracy but consume a lot of energy during the communication and the processing at the node and the sink, and thus decrease the lifetime of the WSN. Therefore, the elimination of redundant measures and reducing the communication cost are considered as essential characteristics during design the WSNs. In this article, a Distributed Data Aggregation (DiDA) protocol for prolonging the lifetime of WSNs is suggested. DiDA protocol is an energy efficient approach for a clustered network. DiDA works into cycles and each cycle aggregates and reduces data dimensionality by using an Adaptive Piecewise Constant Approximation (APCA) method. DiDA was successfully evaluated using OMNeT++ network simulator and based on sensed data of a real sensor network. Percentage of Sent data to the Cluster Head (CH), data accuracy, and energy consumption are the performance metrics applied to assess the effectiveness of the DiDA protocol. The conducted simulation results show that the proposed DiDA protocol decreases the consumed energy and extending the network lifetime, in comparison with a method without using data aggregation technique, whilst keeping the sensed data quality at the sink node